For part (b), `ftext[(]x text[)]=gtext[(]x text[)]htext[(]x text[)]`, where `gtext[(]x text[)]=x` and `htext[(]x text[)]=x^2`. Since `ftext[(]x text[)]=x^3`, we know `f'text[(]x text[)]=3x^2. On the other hand, `g'text[(]x text[)]=1` and `h'text[(]x text[)]=2x`. So, it is clear that `f'text[(]x text[)]` is not `g'text[(]x text[)]h'text[(]x text[)], i.e., the obvious candidate for a product formula is wrong. Parts (a) and (c) show the same thing.
We will see shortly that the correct formula is
For example, in part (b),
Let's try this out for part (c). Here, `ftext[(]x text[)]=gtext[(]x text[)]htext[(]x text[)]`, where `gtext[(]x text[)]=e^(2x)` and `htext[(]x text[)]=e^(3x)`. For this example,
On the other hand, `ftext[(]x text[)]=e^(5x)` and `f'text[(]x text[)]=5e^(5x)`.